Kidney Exchange over the Blood Group Barrier - Tommy Andersson; Jörgen Kratz (Lund University, School of Economics and Management, Department of Economics, 2016)
Medical technology making kidney transplantation over the blood group barrier possible is now a reality. This paper investigates how such technology should be implemented when designing pairwise kidney exchange programs. The possibility to receive a kidney transplant from a blood group incompatible donor motivates an extension of the preference domain, allowing patients to distinguish between compatible donors and half-compatible donors (i.e., blood group incompatible donors that are made compatible using immunosuppressive drugs). It is demonstrated that the number of transplants can be increased by providing an incentive for patients with half-compatible donors to participate in kidney exchange programs. The results also suggest that the technology is beneficial for patient groups that are traditionally disadvantaged in kidney exchange programs (e.g., blood group O patients). The positive effect of allowing transplants over the blood group barrier is larger than the corresponding effects of including compatible patient-donor pairs and allowing three-way exchanges in addition to pairwise exchanges.
Keywords: C78; D02; D63; D78; 330; market design; pairwise kidney exchange; blood group incompatibility; priority matchings; half-compatibility priority matchings